A pedagogia inaciana e a eficácia da mediação docente no favorecimento à aprendizagem - Santos, Geise Alessandra Rampazo (Universidade do Vale do Rio dos Sinos, 2019)
The present study is an attempt to establish relationships between the Ignatian Pedagogy and the Mediated Learning Experience (EAM), focusing on the teacher / mediator, his / her posture and attitudes. It seeks to answer the following problem question: what aspects of Ignatian pedagogy converge to ideas about mediated learning experience? In its general objective, the research points out some principles of Ignatian pedagogy and its relation with the experience of mediated learning - EAM. The specific objectification is about a threefold epistemological movement: lecturing on the principles of Ignatian pedagogy; to approach aspects of teacher mediation according to Feuerstein's ideas; points between the principles of Ignatian pedagogy and Feuerstein's ideas. The research is bibliographical, with theoretical main contribution in Klein (1999), Sasson (2006), Gonçalves and Vagula (2012), and Guidini (2016). In his considerations, he records that the Ignatian Pedagogy considers the teacher as a mediator of knowledge, as well as Feuerstein, whose goal is human adaptation and development in all dimensions. The study contributes with reflections on the Ignatian Pedagogy and the EAM applied to the formative field of teachers, as well as the exercise of the pedagogical practice in the School of Basic Education.
Keywords: Pedagogia inaciana; Experiência de aprendizagem mediada; Professor mediador; Ignatian pedagogy; Mediated learning experience; Mediator teacher